'She Does Paint Most Delightfully': Lady Caroline Lamb's Artistic Accomplishments. Issue 1 (1st June 2022) - Paterson-Morgan, Emily
Abstract : Lady Caroline Lamb has often been dismissed as an overly melodramatic stalker, unhealthily obsessed with the lover who rejected her. Despite publishing numerous novels and writing a number of extremely adroit satirical poems, her sole claim to popular contemporary recognition is a brief affair with a newly-famous poet during the spring of 1812. Even her most famous novel, Glenarvon, tends to attract readers seeking scurrilous autobiographical tidbits rather than those drawn by its literary merits. Her critical reception is often similarly imbalanced – heavily weighted to prioritise her interactions with Lord Byron, she is disparagingly referred to as a hysterical illiterate in a number of studies. However, Lamb's two commonplace books offer a rather different perspective, preserving many examples of her artistic skill and keen (satirical) eye for natural and social minutiae. Moreover, through her choice of topic, these drawings, sketches and paintings allow us glimpses of Lamb's life unfiltered by the Byronic lens through which she is typically viewed. This note looks at a small selection of the artworks from Lamb's green commonplace book, reproduced with the kind permission of the National Library of Scotland.